A comparison of socio-behavioral risk factors between HIV-infected and non-infected older adults in Northern Thailand - Arunrat Tangmunkongvorakul (2019)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. There is a shift in the demographic profile of people living with HIV toward older age groups. The current study compares alcohol use, smoking, and physical exercise between HIV-infected and non-infected older adults recruited in 12 community hospitals in Chiang Mai Province, Northern Thailand. Participants in the two groups were 50 years and above, matched by age and gender. The sample included 364 participants in each of the groups. Older adults living with HIV were less likely to report drinking alcohol in the past year (AOR, 0.55; CI, 0.34–0.89, P = 0.015) and more likely to report being currently engaged in physical activities (AOR, 2.58; CI, 1.77–3.76, P < 0.001). There was no difference between the two groups in terms of “current smoking status”. Older adults living with HIV were healthier than their non-infected counterparts in terms of the socio-behavioral risks.